Prostate-specific Membrane Antigen Heterogeneity and DNA Repair Defects in Prostate Cancer - Paschalis, Alec; Sheehan, Beshara; Riisnaes, Ruth; Rodrigues, Daniel Nava; Gurel, Bora; Bertan, Claudia; Ferreira, Ana; Lambros, Maryou B.K.; Seed, George; Yuan, Wei; Dolling, David; Welti, Jon C.; et al. (European urology, 2019)
Prostate-specific membrane antigen (PSMA; folate hydrolase) prostate cancer (PC) expression has theranostic utility. To elucidate PC PSMA expression and associate this with defective DNA damage repair (DDR). Membranous PSMA (mPSMA) expression was scored immunohistochemically from metastatic castration-resistant PC (mCRPC) and matching, same-patient, diagnostic biopsies, and correlated with next-generation sequencing (NGS) and clinical outcome data. Expression of mPSMA was quantitated by modified H-score. Patient DNA was tested by NGS. Gene expression and activity scores were determined from mCRPC transcriptomes. Statistical correlations utilised Wilcoxon signed rank tests, survival was estimated by Kaplan-Meier test, and sample heterogeneity was quantified by Shannon's diversity index. Expression of mPSMA at diagnosis was associated with higher Gleason grade (p=0.04) and worse overall survival (p=0.006). Overall, mPSMA expression levels increased at mCRPC (median H-score [interquartile range]: castration-sensitive prostate cancer [CSPC] 17.5 [0.0–60.0] vs mCRPC 55.0 [2.8–117.5]). Surprisingly, 42% (n=16) of CSPC and 27% (n=16) of mCRPC tissues sampled had no detectable mPSMA (H-score <10). Marked intratumour heterogeneity of mPSMA expression, with foci containing no detectable PSMA, was observed in all mPSMA expressing CSPC (100%) and 37 (84%) mCRPC biopsies. Heterogeneous intrapatient mPSMA expression between metastases was also observed, with the lowest expression in liver metastases. Tumours with DDR had higher mPSMA expression (p=0.016; 87.5 [25.0–247.5] vs 20 [0.3–98.8]; difference in medians 60 [5.0–95.0]); validation cohort studies confirmed higher mPSMA expression in patients with deleterious aberrations in BRCA2 (p<0.001; median H-score: 300 [165–300]; difference in medians 195.0 [100.0–270.0]) and ATM (p=0.005; 212.5 [136.3–300]; difference in medians 140.0 [55.0–200]) than in molecularly unselected mCRPC biopsies (55.0 [2.75–117.5]). Validation studies using mCRPC transcriptomes corroborated these findings, also indicating that SOX2 high tumours have low PSMA expression. Membranous PSMA expression is upregulated in some but not all PCs, with mPSMA expression demonstrating marked inter- and intrapatient heterogeneity. DDR aberrations are associated with higher mPSMA expression and merit further evaluation as predictive biomarkers of response for PSMA-targeted therapies in larger, prospective cohorts. Through analysis of prostate cancer samples, we report that the presence of prostate-specific membrane antigen (PSMA) is extremely variable both within one patient and between different patients. This may limit the usefulness of PSMA scans and PSMA-targeted therapies. We show for the first time that prostate cancers with defective DNA repair produce more PSMA and so may respond better to PSMA-targeting treatments. Membranous prostate-specific membrane antigen (mPSMA) expression is upregulated in many, but not all, prostate cancers. Importantly, prostate-specific membrane antigen (PSMA) expression demonstrates marked intra- and interpatient heterogeneity, limiting the clinical utility of PSMA theranostics. Defective DNA repair gene aberrations are associated with significantly higher mPSMA expression levels in metastatic castration-resistant prostate cancer and may serve as predictive biomarkers for PSMA-targeted therapies.